Exploring the mechanism of trait depression and cognitive impairment on the formation of among individuals with methamphetamine use disorder under varying degrees of social support - Wang, Wei; Sun, Guangsheng; Li, Chen; Qiu, Cunxi; Fan, Junyi; Jin, Yuhan (Frontiers in Public Health, 2025)
BackgroundMethamphetamine stands as one of the most widely abused drugs globally. Methamphetamine Use Disorder not only impairs the physical and mental wellbeing of addicts but also elevates their risk of suicide. Despite the high suicide rate among individuals with methamphetamine use disorder, research on their clinical characteristics and suicide risk factors remains scarce. Therefore, it is imperative to investigate the risk factors associated with suicidal ideation in individuals with methamphetamine use disorder.MethodsEmploying Respondent Driven Sampling (RDS), a total of 11,825 individuals with methamphetamine use disorder were selected from April to May 2023 in Guangdong, China. The individuals with methamphetamine use disorder were assessed using the Beck Scale for Suicide Ideation (BSSI), and the detection rate of suicidal ideation among these patients was 23.92%. The Bayesian Mindsponge Framework (BMF) analysis was utilized to examine the risk factors for suicidal ideation among these individuals.ResultsThe result revealed that trait depression and cognitive impairment are positively correlated with suicidal ideation in people, whereas social support has a moderating effect on the relationship between trait depression and cognitive impairment with suicidal ideation.ConclusionSuicidal ideation in individuals with methamphetamine use disorder is influenced by a multitude of factors, including family, society, and stress. Consequently, comprehensive intervention measures are essential to address this issue.